A review on miRNAs as new biomarkers for colorectal cancer - Kiyanoush Mohammadi; Reza Safaralizadeh (Fasa University of Medical Sciences, 2019)
Background & Objective: Since colorectal cancer does not often have phenotypic symptoms in the early stages, the study of biomarkers for the diagnosis and prognosis of the tumor is very important. MicroRNAs are one of the most important biomarkers which attract the attention of many researchers due to a variety of reasons, including their non-invasive nature; these molecules are a group of non-coding small RNAs that suppress gene expression by interacting with mRNA at the post-transcriptional level. The objective of the present study is to investigate the potential of microRNAs as a biomarker for colorectal cancer and evaluating their changes at different pathophysiological and molecular levels of cancer. Methods: In this review study, we explored the PubMed, Google Scholar and Scopus databases to investigate the role of microRNAs in colorectal cancer. Conclusion: The discovery of the fact that microRNAs are able to act as oncogene or tumor suppressor has led to the initiation of extensive investigations on cancer, resulting in the identification of various microRNAs involved in carcinogenesis and its progression. Various studies have shown that microRNAs are dysregulated in tissue samples and body fluids of people with colorectal cancer. MicroRNAs in body fluids such as serum, plasma, and fecal specimens are chemically stable, and their diagnosis is easy, so by studying microRNAs in colorectal cancer, the initiation, stages, spread, or mechanisms of the tumor can be predicted and notified.